THE INFLUENCE OF OPEN UNEMPLOYMENT AND INFLATION ON THE GROWTH OF THE MIDDLE-CLASS POPULATION IN INDONESIA - I Wayan Suparta (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of open unemployment and inflation on the growth of the middle-class population in Indonesia. This relationship is crucial as it can significantly impact a country's overall economic conditions. The variables observed include the middle-class population, open unemployment, and inflation. The data used are time series data spanning from 1994 to 2023. The analytical methods employed consist of data stationarity tests, Johansen cointegration tests, the Vector Error Correction Model (VECM), Impulse Response Function (IRF), and Variance Decomposition. The results indicate that, in the long term, open unemployment and inflation have a significant impact on the growth of the middle-class population in Indonesia. Inflation has a negative effect, suggesting that rising inflation can hinder middle-class growth due to a decline in purchasing power and economic welfare. Conversely, open unemployment exerts a positive influence, which may reflect structural dynamics in the labor market and changes in income patterns within society. However, in the short term, neither inflation nor open unemployment has a significant impact on the growth of the middle-class population. The equilibrium adjustment analysis reveals that inflation plays a critical role in correcting deviations toward long-term equilibrium, whereas open unemployment does not significantly contribute to this process. This study underscores the importance of controlling inflation and creating quality employment opportunities to support the growth of the middle class in Indonesia.